Assassin of reality : a novel - Di︠a︡chenko, Marina; Di︠a︡chenko, Serhiĭ, 1945-2022 (Di︠a︡chenko, Marina. Metafantastika., 2023)
The sequel to the highly acclaimed Vita Nostra takes readers to the next stage in Sasha Samokhina's journey in a richly imagined world of dark academia in which grammar is magic--and not all magic is good.